Research on Elite Capture under the Background of Digital Rural Construction - Jin, Xiaolin (Journal of Global Economy, Business and Finance, 2024)
Digital rural construction is an important driving force to promote rural revitalization and common prosperity, and the project to the countryside is an important way to achieve common prosperity. However, under the background of digital rural construction, there is still the problem of elite capture in the project to the countryside. By analyzing the participants, expression forms and influencing factors of elite capture, the governance strategies are put forward.